Magnetic anisotropy, magnetoelastic coupling, and the magnetic phase diagram of Ni0.25Mn0.75TiO3 - Elghandour, Ahmed; Gries, Lukas; Singer, Lennart; Hoffmann, Marco; Spachmann, Sven; Uhlarz, M.; Dey, K.; Klingeler, Rüdiger (Physical review, 2023)
Thermodynamic and magnetic studies on high-quality single crystals are used to investigate the magnetic phase diagram and magnetostructural coupling in the mixed-spin system Ni0.25Mn0.75TiO3. Clear anomalies in the thermal expansion at the spin ordering and spin reorientation temperatures,TN and TR, evidence pronounced magnetoelastic effects. The magnetic entropy is released mainly above TN implying considerable short range magnetic order up to about 4×TN. This is associated with a large regime of negative thermal expansion of the c axis. Both TN and TR exhibit the same sign of uniaxial pressure dependence, which is positive (negative) for pressure applied along the b (c) axis. The magnetic phase diagrams are constructed and the uniaxial pressure dependencies of the ordering phenomena are determined. For magnetic fields B∥b axis, a sign change and splitting of anomalies implies further magnetic phases. In addition to short-range magnetic order well above TN, competing anisotropies yield a glasslike behavior as evidenced by a maximum in AC-χ (TSG≃3.7 K) and quasilinear temperature dependence of cp. High-field magnetization up to 50 T demonstrates that in addition to antiferromagnetically ordered spins there are also only weakly coupled moments at 2 K with a sizable amount of about 15% of all Mn2+ spins present in the material. The observed changes in the pressure dependence and the magnetostrictive effects shed light on the recently observed flop of electric polarization from P∥c to P∥a [Phys. Rev. B 90, 144429 (2014)], in particular, suggesting that the magnetoelectric effect is not directly related to magnetostriction.
Im Text sind "0.25", "0.75" und "3 tiefgestellt
Gesehen am 16.10.2023